Knowledge on Food Safety and Food-Handling Practices of Street Food Vendors in Ejisu-Juaben Municipality of Ghana - Raymond Addo-Tham; Emmanuel Appiah-Brempong; Hasehni Vampere; Emmanuel Acquah-Gyan; Adjei Gyimah Akwasi (Advances in Public Health)
Street foods have become a major source of cooked food for most households and individuals in many developing countries including Ghana. However, the rising concern about food-borne illness has questioned the knowledge of the street food vendors to constitute safety practices for food handling. This study assessed the knowledge of street food vendors on food safety and food-handling practices in the Ejisu-Juaben Municipality of Ghana. The study used a cross-sectional mixed approach involving 340 participants selected by simple random sampling. A structured questionnaire and an observational checklist were used to collect data and analyzed using STATA version 12. The results indicated that 98.8% of the food vendors had good knowledge on food safety and handling. The knowledge on food safety was associated with training (p value ≤0.011), license status (p value ≤0.002), marital status (p value <0.001), and religion (p value ≤0.038). Good food-handling practices were associated with training (p value ≤0. 001) and license (p value ≤0.002) and not their educational levels. The study found training of food vendors as the most effective way to increase knowledge on food safety and enhance food-handling practices. The study recommended for collaborations of municipal assemblies with other agencies to strengthen, sustain, and organize regular training programs for new entrants and existing food vendors as well as retraining of trainers to equip them adequately with knowledge and skills to enable them effectively facilitate training programs for food vendors.